Women’s Access To Justice In Cases Of Domestic Violence Under Indian Legislations: Barriers And Solutions (Cuestiones de Fisioterapia, 2025)
While married women hardly ever see justice today, much less because they are left without proper support, domestic violence has continued to be such a widespread element of India's backdrop as BNS 2023 aspires to bring forth an updated legal framework aimed at addressing many forms and dimensions of violence against women, covering domestic abuse also.